Physical activity in the elderly is associated with improved executive function and processing speed: the LADIS Study - Frederiksen, Kristian Steen; Bäzner, Hansjörg (International journal of geriatric psychiatry, 2014)
Objectives: Physical activity reduces the risk of cognitive decline but may affect cognitive domains differently. We examined whether physical activity modifies processing speed, executive function and memory in a population of non-dementia elderly subjects with age-related white matter changes (ARWMC). Methods: Data from the Leukoaraiosis And DISability (LADIS) study, a multicenter, European prospective cohort study aimed at examining the role of ARWMC in transition to disability, was used. Subjects in the LADIS study were clinically assessed yearly for 3 years including MRI at baseline and 3-year follow-up. Physical activity was assessed at baseline, and cognitive compound scores at baseline and 3-year assessment were used. Results: Two-hundred-eighty-two subjects (age, y (mean (SD)): 73.1 (±5.1); gender (f/m): 164/118); MMSE (mean (SD)): 28.3 (±1.7)) who had not progressed to MCI or dementia, were included. Multiple variable linear regression analysis with baseline MMSE, education, gender, age, stroke, diabetes and ARWMC rating as covariates revealed that physical activity was associated with better scores at baseline and 3-year follow-up for executive function (baseline: β: 0.39, 95% CI: 0.13-0.90, p = 0.008; follow-up: β: 0.24, 95% CI: 0.10-0.38, p = 0.001) and processing speed (baseline: β: 0.48, 95% CI: 0.14-0.89, p = 0.005; follow-up: β: 0.15, 95% CI: 0.02-0.29, p = 0.02) but not memory. When including baseline cognitive score as a covariate in the analysis of 3-year follow-up scores, executive function remained significant (β: 0.11, 95% CI: 0-0.22, p = 0.04). Conclusion: Our findings confirm previous findings of a positive effect of physical activity on cognitive functions in elderly subjects, and further extends these by showing that the association is also present in patients with ARWMC.
Gesehen am 23.01.2018